Health Care Expenditure Burden of Cancer Care in the United States - Joohyun Park PhD; Kevin A. Look PharmD, PhD (SAGE Publishing, 2019)
Using nationwide data, this study estimated and compared annual health care expenditures per person between noncancer and cancer patients, and among patients with the 4 most common cancers. Two-part models were used to estimate mean expenditures for each group by source of payment and by service type. We found that cancer patients had nearly 4 times higher mean expenditures per person ($16 346) than those without cancer ($4484). These differences were larger among individuals aged 18 to 64 years than those ≥65 years. Medicare was the largest source of payment for cancer patients, especially among those ≥65 years. Among the 4 most common cancers, the most costly cancer was lung cancer. Ambulatory care visits accounted for the majority of health care expenditures for those with breast cancer, while for those with other cancers, inpatient services also contributed to a significant portion of expenditures especially among younger patients. This study demonstrates that cancer patients experience a substantially higher health care expenditure burden than noncancer patients, with lung cancer patients having the highest expenditures. Expenditure estimates varied by age group, source of payment, and service type, highlighting the need for comprehensive policies and programs to reduce the costs of cancer care.